PENDAMPINGAN BUDIDAYA LARVA TENTARA LALAT HITAM (HERMETIA ILLUCENS) KOMUNITAS PETERNAK SAPI DI SANGATTA, KALIMANTAN TIMUR - Ari Sanjaya; Didit Suprihanto; Wulan Sari; Rudianto Rudianto; Rudy Agung Nugroho; Retno Aryani; Hetty Manurung; Muhammad Fauzi Arif; Iyut Jaya Toimsar (LP2M Universitas Hasanuddin, 2024)
Black Soldier Fly larvae commonly known as maggot (Hermetia illucens), are currently gaining momentum to convert organic waste. Using bioconversion technology of organic waste with maggot, will not only help in decomposing waste but also the results of cultivation can improve the economy of society. This community service aimed to provide assistance in maggot cultivation for the cattle breeder community, Sangatta City, East Kalimantan province, so that they are familiar with and able to cultivate maggot, especially for producing high protein feed ingredients. The present community service activity was attended by a group of cattle breeders from the Sangatta area, East Kalimantan, and accompanied by a community service team from Mulawarman University. The activity lasted for three months and the implementation was carried out using the method of material presentation, discussion, question and answer, and the practice of maggot cultivation. The activity was carried out at the house of the Sangatta cattle farmer, East Kalimantan. As a result of the activity, cattle breeders have been able to start maggot cultivation and provide an evaluation that the activity is very important because it adds new insight and understanding about maggot cultivation, especially for food security in the area around the capital of the archipelago, Indonesia. — Larva lalat tentara hitam atau dikenal awam sebagai belatung atau maggot dengan nama ilmiah (Hermetia illucens), saat ini popular dibudidayakan untuk merombak limbah organik. Dengan adanya teknologi biokonversi limbah organik dengan maggot, maka tidak hanya membantu dalam merombak limbah namun juga hasil budidaya dapat meningkatkan perekonomian. Pengabdian kepada masyarakat kali ini bertujuan memberikan pendampingan budidaya maggot bagi komunitas peternak sapi Sangatta, Kalimantan Timur, agar mengenal dan mampu membudidayakan maggot dan menghasilkan larva yang mengandung bahan pakan berprotein tinggi. Pengabdian diikuti oleh kelompok peternak sapi dari wilayah Sangatta, Kalimantan Timur dan didampingi oleh tim pengabdi dari Universitas Mulawarman. Kegiatan berlangsung total selama 3 bulan dan pelaksanaan dilakukan dengan metode presentasi materi, diskusi, tanya jawab dan praktek budidaya maggot. Kegiatan dilaksanakan di rumah peternak sapi Sangatta, Kalimantan Timur. Hasil kegiatan, peternak sapi telah mampu memulai budidaya maggot dan memberikan evaluasi bahwa kegiatan sangat penting karena menambah wawasan dan pemahaman baru tentang budidaya maggot terutama untuk ketahanan pangan di wilayah sekitar Ibukota Negara Nusantara, Indonesia.